Asean-latin America bilateral relations: symbiosis or antagonist? - Zaini Othman; Mohd Mahadee Ismail (IDOSI Publications, 2016)
In the context of Southeast Asia, Singapore (since 1970s) was the earliest country that established a serious bilateral relation with Latin American region, particularly with the countries known as Latin America-Bloc 6 States. Ever since, a bilateral relation between the two regions has become increasingly strong as Chile and Peru accelerate free trade talks with several Southeast Asian countries such as Vietnam, Singapore, Thailand and Malaysia. Thus, based on the latest bilateral development between the two regions, it is a very significant to study a comprehensive roadmap of bilateral relations between the region in the context of the present international political developments, either globally or regionally. This article will sketch the nature and form of the bilateral relations between the region (read Southeast Asia and Latin America, in particular to examine whether the positives bilateral relationship that has taken place between the region for the past two decades is a symbiosis or antagonistic in nature.